The Influence of Product Quality, Content Marketing and Bandwagon Effect on Gen Z Consumer Satisfaction in Online Local Fashion Brands - Oktapiyana, Elisha; Arifah, Alfin Nur; Rachmanda, Yudi Setia; Ardiansyah, Ardiansyah (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2026)
The local fashion industry in Indonesia has experienced significant growth in recent years, particularly within the digital realm driven by the dominance of Generation Z as the largest internet user base. However, this rapid growth has created a gap between consumer expectations and the actual products received, which has the potential to undermine consumer satisfaction. This study aims to examine the impact of the bandwagon effect, content marketing, and product quality on Generation Z's satisfaction with local online fashion brands in Tasikmalaya Regency. Using a quantitative approach with an exploratory descriptive design, data were collected through a non-probability sampling method from 100 participants, following rigorous validity and reliability testing. The findings indicate that product quality, content marketing, and the bandwagon effect each partially exert a significant and positive influence on consumer satisfaction. Furthermore, when analyzed simultaneously, all three variables product quality, content marketing, and the bandwagon effect collectively have a significant and positive impact on Generation Z's satisfaction. These results underscore the importance of aligning digital marketing strategies and social trends with actual product standards to maintain and enhance customer satisfaction in the competitive online fashion market.